Penggunaan E-Commerce Di Kalangan Para Pedagang Di Pasar Baru Permai (Sudimampir) Banjarmasin - Yeni Yashella; Laila Azkia (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2024)
Based on DataIndonesia.id (28/02/2023) in 2022 in Indonesia there will be more and more online business actors. This research aims to (1) Find out the motives of traders at Baru Permai Market, Banjarmasin who use e-commerce. (2) Knowing the motives of traders at Baru Permai Market, Banjarmasin who do not use e-commerce. This research uses qualitative research methods. The data sources selected used purposive sampling and the informants in this study were 6 people. Data collection was carried out using observation, interviews and documentation techniques. The data analysis technique in this research uses data reduction techniques, data presentation, and drawing conclusions. The results of the research show that (1) The motives of traders who use e-commerce are because of cheaper prices, to fulfill stock of goods, and a more diverse choice of goods. The objective motive is for promotional activities, and is more flexible. (2) The motives of traders who do not use e-commerce are because they don't know how, it's difficult to access, and it's difficult. The goal motive is not having to buy a quota, and not creating content first. Based on the research results, it is recommended that future researchers use different theories and methods to those used by researchers, taking a different market from Pasar Baru Permai because Sudimampir Market itself is a combination of several markets and sells different goods.